Pengaruh Budaya Organisasi terhadap Kinerja Aparatur di Kantor Desa Bottomallangga Kecamatan Maiwa Kabupaten Enrekang - Nurwidya, Nurwidya; Hariyanti Hamid; Muliani, Muliani; Monalisa Ibrahim (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the influence of organizational culture on the performance of government officials at the Botto Mallangga Village Office, Maiwa District, Enrekang Regency. The research population consists of 1,955 community members who have visited the village office for administrative purposes. The study employs an associative quantitative method with a sample of 95 respondents selected through non-probability sampling. It examines two key variables: variable X (organizational culture) and variable Y (government officials' performance). Data collection methods include observation, questionnaires, and literature review. Data analysis involves validity and reliability tests with the assistance of IBM SPSS Statistics 26.0. The findings indicate that organizational culture has a significant influence on government officials' performance. Recapitulation results show a percentage of 62.75% for organizational culture and 68% for performance, both categorized as good. Factors affecting organizational culture and their impact on performance also scored 65%, classified as good. ANOVA test results reveal an F value of 23.719 with a significance level of 0.000, confirming that the independent variable has a significant impact. With an R square value of 20%, the study suggests that 80% of government officials' performance is influenced by other variables outside this research.